Perlindungan Hak Asasi Manusia terhadap Narapidana Narkotika Sebagai Warga Binaan Pemasyarakat Menurut Undang-Undang Nomor 12 Tahun 1995 Tentang Pemasyarakatan - Sigit Somadiyono; Nella Octaviany Siregar (Universitas Batanghari Jambi, 2019)
This research specifically discusses the human rights of prisoners as prisoners in prison, which in their daily lives must be respected, upheld and protected by the state, the law (in this case the Penitentiary Act to be in line with the Human Rights Act), the government through the apparatus is correctional officers and fellow inmates. Prisoners in their daily life can make mistakes and lives that are in contact with human rights violations. The object of this research is the human rights of inmates as prisoners in prison (WBP). The formulation of the problems in this study are (1) How are the human rights protection arrangements for prisoners in prison according to Law Number 12 of 1995; and (2) How is the implementation of human rights protection for narcotics prisoners in prison in East Tanjung Jabung Regency. This study uses Law Number 12 of 1995 Concerning Corrections and other derivative regulations. The results showed that there were differences in the implementation of human rights protection for prisoners with Law Number 12 of 1995 Concerning Corrections.